Implementasi buku petunjuk praktikum biokimia berbasis inkuiri terbimbing untuk meningkatkan kemampuan kerja ilmiah - Diyah Ayu Widyaningrum; Titik Wijayanti (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2019)
Learning material is one of the facilities needed by students to help them find concepts and answers to their problems. There are various types of learning materials, one of which is a practical guide. Based on observations on learning materials and the learning process of Biochemistry courses at IKIP Budi Utomo Malang shows that there are no practical manuals developed and students' scientific workability is low. The aim of the research is to improve students' scientific work abilities through the implementation of guided inquiry-based biochemistry practicum books. The research method used was Classroom Action Research. Stages of Classroom Action Research include planning, implementing, observing, and reflecting. The research instruments used were interview sheets, observations, and observations of scientific work capabilities and camera documentation. The results showed that there was an increase in students' scientific work abilities through the implementation of guided inquiry-based biochemistry practicum books from cycle I to cycle II in the amount of 36.18% to 88.8% and N-gain values of 0.84 (high criteria). Thus, this research concludes that there is an increase in students' scientific work abilities through the implementation of guided inquiry-based biochemistry practicum books.